2015
DOI: 10.1186/s12889-016-2787-5
|View full text |Cite
|
Sign up to set email alerts
|

All-age hospitalization rates in coal seam gas areas in Queensland, Australia, 1995–2011

Abstract: BackgroundUnconventional natural gas development (UNGD) is expanding globally, with Australia expanding development in the form of coal seam gas (CSG). Residents and other interest groups have voiced concerns about the potential environmental and health impacts related to CSG. This paper compares objective health outcomes from three study areas in Queensland, Australia to examine potential environmentally-related health impacts.MethodsThree study areas were selected in an ecologic study design: a CSG area, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 27 publications
0
26
1
Order By: Relevance
“…In addition to hazard identification studies, a growing body of population based epidemiological studies have investigated associations between living near OG operations and the potential for certain health effects, such as adverse birth outcomes, upper and lower respiratory effects, cancer, and a variety of other health outcomes [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Although these epidemiological studies provide important insights into the potential health effects of at risk populations and assist in prioritizing public health research, one of the main limitations of these studies is the lack of direct quantification of chemical exposures to the observed population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to hazard identification studies, a growing body of population based epidemiological studies have investigated associations between living near OG operations and the potential for certain health effects, such as adverse birth outcomes, upper and lower respiratory effects, cancer, and a variety of other health outcomes [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Although these epidemiological studies provide important insights into the potential health effects of at risk populations and assist in prioritizing public health research, one of the main limitations of these studies is the lack of direct quantification of chemical exposures to the observed population.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, age-specific studies found increasing “Blood/immune” disease admission rates in a CSG study area compared to the other study areas and decreasing rates for one child/adolescent age group [20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…Rates increased for some health outcomes (e.g., “Blood/immune” and “Respiratory”) and age groups (e.g., 0–4, 5–9, 10–14, and 20–34 year old) in the CSG area compared to the other study areas [19,20,21]. This paper focuses solely on the CSG study area to examine whether changes in hospitalisation rates for residents of this area vary over time as a function of CSG development activity (e.g., construction, drilling of wells, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of UNGD and health studies present when this study was designed and conducted, this study was exploratory and examined a range of health outcomes to generate hypotheses for future work that may relate to the putative exposures described above. Previous Australian studies found increased hospitalisation rates for neoplasms and blood/immune diseases for people living in CSG areas compared to a rural/agricultural area and increased hospitalisation rates for congenital anomalies for the CSG area compared to a coal mining area (Werner et al 2016a , b ). This exploratory analysis thus builds on those previous Australian studies to examine age-specific hospitalisation rates for children and adolescents aged 0–19 years old in a CSG study area compared to two other study areas (coal mining and rural/agricultural) in Queensland over the period 1995–2011.…”
Section: Introductionmentioning
confidence: 93%